Aquatic nitrous oxide reductase gene (nosZ) phylogeny and environmental distribution - Intrator, Naomi; Jayakumar, Amal; Ward, Bess B. (Frontiers in Microbiology, 2024)
Nitrous oxide (N2O) is a potent greenhouse gas and a major cause of ozone depletion. One-third of atmospheric N2O originates in aquatic environments. Reduction of N2O to dinitrogen gas (N2) requires the nitrous oxide reductase enzyme, which is encoded by the gene nosZ. Organisms that contain nosZ are the only known biological sinks of N2O and are found in diverse genera and a wide range of environments. The two clades of nosZ (Clade I and II) contain great diversity, making it challenging to study the population structure and distribution of nosZ containing organisms in the environment. A database of over 11,000 nosZ sequences was compiled from NCBI (representing diverse aquatic environments) and unpublished sequences and metagenomes (primarily from oxygen minimum zones, OMZs, where N2O levels are often elevated). Sequences were clustered into archetypes based on DNA and amino acid sequence identity and their clade, phylogeny, and environmental source were determined. Further analysis of the source and environmental distribution of the sequences showed strong habitat separation between clades and phylogeny. Although there are more Clade I nosZ genes in the compilation, Clade II is more diverse phylogenetically and has a wider distribution across environmental sources. On the other hand, Clade I nosZ genes are predominately found within marine sediment and are primarily from the phylum Pseudonomonadota. The majority of the sequences analyzed from marine OMZs represented distinct phylotypes between different OMZs showing that the nosZ gene displays regional and environmental separation. This study expands the known diversity of nosZ genes and provides a clearer picture of how the clades and phylogeny of nosZ organisms are distributed across diverse environments.